2021
DOI: 10.1016/j.isci.2021.102100
|View full text |Cite
|
Sign up to set email alerts
|

A T cell repertoire timestamp is at the core of responsiveness to CTLA-4 blockade

Abstract: Response to ICI is associated with pretreatment TCR repertoire in mice TCR repertoire goes through distinct, ICIdependent changes with time Tumor size and its response to ICI can be tracked by TCR repertoire metrics A single time point is found to be a focal point of the immune response

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 52 publications
(59 reference statements)
1
9
0
Order By: Relevance
“…These findings encourage non-invasive and early monitoring of patients receiving ICIs to anticipate clinical response to the treatment. The importance to frame early time points and quantify the dynamics of TCR repertoire during immunotherapy, was also confirmed in a syngeneic mouse model of CRC, where the authors identified a transient and initial increase in clonality in parallel with a decreased diversity which gradually receded [ 102 ]. More recently, Wucherpfennig group published an elegant study where, by designing a powerful experimental set up, the authors temporally characterized the response of T-cell subsets to anti-PD-1 and anti-CTLA-4 treatments, both in the tumor and blood of head and neck cancer patients, in a neoadjuvant setting [ 103 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings encourage non-invasive and early monitoring of patients receiving ICIs to anticipate clinical response to the treatment. The importance to frame early time points and quantify the dynamics of TCR repertoire during immunotherapy, was also confirmed in a syngeneic mouse model of CRC, where the authors identified a transient and initial increase in clonality in parallel with a decreased diversity which gradually receded [ 102 ]. More recently, Wucherpfennig group published an elegant study where, by designing a powerful experimental set up, the authors temporally characterized the response of T-cell subsets to anti-PD-1 and anti-CTLA-4 treatments, both in the tumor and blood of head and neck cancer patients, in a neoadjuvant setting [ 103 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, since a phenotypical change, such as reduction in tumor size, can occur some time after the peak of the immunological response, it can be difficult to create a snapshot of the immune state at the most relevant time. Moreover, the high variability in the favorable reaction of cancers to immunotherapy, makes it even challenging for researcher to quantify the true dynamics of the immune response 21 . Animal health and ethics.…”
Section: Data Descriptor Openmentioning
confidence: 99%
“…Clustering highly similar TCRβ sequences has been applied to understand how ICT changes TCRβ repertoire structure (the number and size of such clusters) (40,41). TCRβs clusters can be linked to TIL phenotype (42,43), and possibly tumor antigen-specificity.…”
Section: Ict Responders Exhibit Early Clonal Expansion Of Tumor-antig...mentioning
confidence: 99%